An Exploration of the Expertness of Outside Informants - Chen, Ming‐Jer; Farh, Jiing‐Lih; MacMillan, Ian C. (Academy of Management Journal, 1993)
This study reviews the use of outside informants-individuals not employed in the firm being studied-in strategy research reported in major journals. We empirically explored the expertness of these informants in terms of interrater reliability and accuracy of their ratings compared to those provided by insiders. Four groups of outside informants in the airline industry-consultants, security analysts, stakeholders, and academics- and senior airline executives whose companies initiated certain competitive moves rated strategic attributes associated with those moves. Informants in each group manifested high interrater reliability. Of the outsiders, analysts were the most accurate and were highly reliable, and academics were highly reliable and as accurate as consultants and stakeholders.